Decision Analysis of ANH Gas Field Using Value Focused Thinking and AHP - Manurung, Adolf S. P.; Putro, Utomo Sarjono (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to obtain the best gas field development scenario based on company values. Research Methodology: This research used qualitative methods obtained from interviews, questionnaires, and discussions. The data obtained were analyzed by researchers with a focus on the content and the relationship between one content and another. This method is used in the value-focused thinking process to determine goals, criteria, and alternative solutions. In addition to qualitative methods, quantitative analysis was performed using the Analytic Hierarchy Process method. This method is used to determine the ranking of project selection criteria and sub-criteria and to determine the best field development scenario. Results: The Project Profitability criterion has the largest weight score of 0.529, while the most important sub-criteria are the Profitability Index (PI) ratio and Net Present Value (NPV), with global weight scores of 0.266 and 0.263, respectively. The selected solution based on the analysis was scenario two with a weight score of 0.477 and an inconsistency value of 0.05. The scope of work for this scenario is drilling nine wells, building a pipeline, and installing a compressor, which is divided into two stages, starting with the MP-HP compressor and the LP-MP compressor. Conclusions: This study applied VFT and AHP methods to evaluate gas field development scenarios, considering criteria such as cumulative production, cost, profitability, and risk. Profitability emerged as the most influential criterion, with the Profitability Index and Net Present Value being the highest-ranked sub-criteria. Scenario 2 was identified as the optimal development plan, involving nine wells, staged compressor installations, and pipeline construction. Limitations: The values of reserves, production, and economic data were slightly modified due to company policies but did not change the qualitative nature of the data. An interview, Focused Group Discussion, and pairwise comparison questionnaire were distributed to Subject Matter Experts who are knowledgeable and involved in decision making in the company. Contribution: This research provides a reference for companies who want to know how to make the right decisions according to company values, particularly in the upstream oil and gas industry.